THE ROLE OF PUBLIC SECTOR BANKS IN INDIA'S ECONOMIC DEVELOPMENT - Sudarshan P; Hegade S, Vidyadhara (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Public Sector Banks (PSBs) have been instrumental in shaping India's economic development since independence. As government-owned financial institutions, PSBs hold a pivotal role in promoting inclusive growth, mobilizing savings, and directing credit to priority sectors like agriculture, small-scale industries, and infrastructure. Their mandate extends beyond profitability to include social and developmental responsibilities, thereby distinguishing them from private sector banks. The nationalization of banks in 1969 and 1980 marked a transformative phase, significantly expanding banking reach in rural and underserved regions. Through widespread branch networks and tailored financial products, PSBs have facilitated financial inclusion, implemented poverty alleviation programs, and supported government-led initiatives such as the Pradhan Mantri Jan Dhan Yojana. Moreover, PSBs have played a critical role in stabilizing the Indian economy during financial crises, including the global financial meltdown of 2008 and the COVID-19 pandemic. They have also supported job creation, promoted regional development, and contributed to the growth of capital markets. Despite challenges such as rising non-performing assets (NPAs), technological disruption, and governance issues, PSBs continue to serve as key drivers of economic progress. Ongoing reforms, consolidation efforts, and digital modernization are aimed at enhancing their efficiency and competitiveness. As India pursues its ambition to become a $5 trillion economy, the role of PSBs remains central to achieving sustainable and equitable development. Their capacity to balance commercial viability with social objectives makes them indispensable to the national economic agenda. This paper explores the multifaceted contributions of Public Sector Banks to India’s economic development, emphasizing their evolution, achievements, challenges, and the path forward.